Form and Function of Lerlote in A Traditional Wedding Ceremony in Manuweri Village, Babar Timur Sub District, Maluku Barat Daya District - Emtamoile, Martalus; Pattiasina, Petrus Jacob; Somelok, Grace (Universitas Pattimura, 2022)
The purpose of this research is to describe the form and function of lerlote in the traditional wedding ceremony in Manuweri Village, East Babar District, Southwest Maluku Regency. The research method used is a descriptive qualitative method using oral literature review. The data in this study are the form and function of the lerlote in traditional wedding ceremonies. The data source in this study was obtained from informants at each stage of the traditional wedding ceremony process. The data collection techniques used in this study are: (1) observation, (2) interviews, (3) recordings, (4) field notes, and (5) documentation. Based on the results of this study, it can be concluded that the forms and functions of lerlote in the traditional wedding ceremony in Manuweri Village are: (1) game songs, (2) truly lyrical folk songs, (3) spiritual and religious folk songs, (4) folk songs for giving advice, and (5) regional songs and songs for people with specific occupations. Meanwhile, in terms of function, the lottery is: (1) entertainment function, (2) information function, and (3) educational function.